Successful Treatment of Unremitting Gastro-Intestinal Haemorrhage & Rashes of Henoch-Schӧnlein Purpura with Colchicine & Cryoprecipitate: A Case Report - Huque, Syed Saimul; Amaan, Abdullahel; Mamun, Abdullah-Al; Jesmin, Tahmina; Begum, Afroza; Roy, Ranjit Ranjan; Uddin, Golam Muin (Journal of Pediatric Nephrology, 2021)
Severe gastrointestinal manifestations and rashes of Henoch Schonlein Purpura (HSP) may not always respond to prednisolone or other immunosuppressive agent. Though reduced factor XIII may play a role in gastrointestinal manifestations but its role in management of skin rashes is uncertain. Here, we reported a case treated with different immunosuppressive agents but didn`t respond. Thereafter, despite having the normal factor XIII assay, the unremitting GI symptoms and skin rashes, has improved after prescribing colchicines & infusion of Cryoprecipitate containing factor XIII.